Cryptosporidium Infections in Africa—How Important Is Zoonotic Transmission? A Review of the Evidence - Robertson, Lucy J.; Johansen, Øystein Haarklau; Kifleyohannes, Tsegabirhan; Efunshile, Akinwale Michael; Terefe, Getachew (Frontiers in Veterinary Science, 2020)
Cryptosporidium, a protozoan parasite in the phylum Apicomplexa, is the etiological agent of cryptosporidiosis, an intestinal infection characterized by profuse watery diarrhea. Over 30 species of Cryptosporidium are recognized, some host specific whereas others infect a broader host range. Cryptosporidium hominis and Cryptosporidium parvum are the species most commonly associated with human infection; C. hominis is largely associated only with human infections, but C. parvum is also associated with infection in animals, particularly young ruminants. In some regions, cryptosporidiosis is a serious veterinary problem, particularly for calves and lambs. Many outbreaks of human cryptosporidiosis have been associated with zoonotic transmission following contact with infected animals. In Africa, where cryptosporidiosis is a major contributor to pediatric morbidity and mortality, evidence suggests transmission is principally anthroponotic. Given the frequent close contact between humans and animals in Africa, this apparent predominance of human-to-human transmission is both interesting and puzzling. Here, after a brief “text book” introduction to the parasite, we consider in separate sections the different aspects of relevance to Cryptosporidium transmission in African countries; describing different aspects of the various species and subtypes in human and animal infections, considering livestock management practices, and looking for any “hot spots” where zoonotic transmission has apparently occurred. Finally, we gather these different strands of evidence together to assess the reasons behind the apparent predominance of anthroponotic transmission in Africa. Reviewing the available evidence provides an opportunity to re-think transmission pathways, not only in Africa but also elsewhere, and also to pose questions. Does the predominance of human-to-human transmission reflect an absence of zoonotic C. parvum in African livestock? Are Africans less susceptible to zoonotic Cryptosporidium infection, perhaps resulting from early immunostimulation by C. hominis or due to genetic traits? Is the African environment simply more detrimental to oocyst survival? Will the hypertransmissible subtypes, currently relatively rare in Africa, be introduced, and, if so, will they fade out or establish? Our intention is not only to summarize and consolidate diverse data, but also to provide food for thought regarding transmission of a parasite that exerts a considerable impact on both human and animal health